Modeling of diabetes mellitus-related depression - Li, H.; Zuo, Y.M.; Lei, Y.H.; Xu, R.J.; Wang, Y. (Нейрофизиология, 2014)
Research on the mechanisms of diabetes-related depression is limited by the lack of sufficiently adequate animal models. Among 80 rats, we formed four groups: (i) normal (N, control), (ii) with streptozotocin (STZ)-induced diabetes mellitus (group Dm), (iii) with a depression model induced by various mild but long-lasting repetitive stressogenic stimulations applied each day during 4 weeks (group D), and (iv) diabetic rats subjected to the combined action of stressogenic influences (group DmD). The latter group (35 animals) was divided into two subgroups, DmD1 subjected to the above chronic stressogenic stimulations, and DmD2 in which diabetic rats were during the above period (4 weeks) kept in isolation. Rats of groups Dm, D, and DmD manifested clear behavioral symptoms of depression. These symptoms were relatively mild in group Dm and much more intense in group DmD. The body mass of rats noticeably decreased in the Dm and D groups and dramatically dropped in the DmD group. In this group, diabetes-related changes in the levels of blood glucose, insulin, and hemoglobin A1C were the greatest. The same relates to the behavioral indices demonstrated by rats in the open field test. The contents of norepinephrine, 5-hydroxytryptamine, and dopamine in the thalamus of rats of groups Dm, D, and DmD were lower than in the norm, and these shifts where most dramatic in the DmD group. The levels of ACTH and cortisol increased in the experimental groups; again, shifts were the greatest in the DmD group. RT PCR and Western blotting showed that the level of NPY protein in the hypothalamus was lower in groups Dm, D, and DmD than that in the norm. Thus, chronic unpredictable stressogenic stimulation or behavioral isolation of diabetic rats significantly aggravates manifestations of depression and stably provides the formation of an adequate animal model of diabetes-related depression. Keeping animals in isolation (subgroup DmD2) is more suitable for empirical studies because of a lower mortality